A 5-Year Retrospective Study on Infant Homicide Presenting as Cot Death: Are We Missing Infant Homicides?. (December 2021) - Tse, Rexson; Ioelu, Leilani; Chen, Matthew; McCarthy, Sinead; Glenn, Charley; Kesha, Kilak; Morrow, Paul; Stables, Simon
Abstract : Abstract: Being found dead in cot or bed is the most common presentation encountered with infant deaths. These deaths are often associated with unsafe sleep environment. The postmortem examination in such cases is often negative, and along with family objections, cultural, and other factors, may lead to a coroner considering not authorizing a postmortem examination. However, not identifying a homicide is a potential risk if a postmortem examination is not performed. This 5-year retrospective study investigated the proportion of infant homicide death initially presenting as cot death. Of a total of 103 cases of infants initially presenting as being found dead in cot or bed, 3 (approximately 3%) were classified as homicides after postmortem examination. During the study period, a total of 9 infant homicides were reported, translating to 33% (3 of 9) of infant homicides presented as cot deaths. Postmortem radiology was a valuable adjunct, but was unable to recognize 2 of the homicide cases with traumatic head injuries (with subdural hemorrhage and brain injury only). We strongly advocate that all infant deaths presenting as cot death require a full postmortem examination.